Delphi assessment of audit and research priorities in an emergency department. (5th February 2020) - O'Donnell, Sinéad M; Carison, Anna; Adams, Jessica; Long, Elliot; Babl, Franz E
Abstract: Objective: Audit and research projects in the ED are important to improve patient care but can be time and resource consuming. We identified and prioritised audit and research topics among multidisciplinary ED staff to fill perceived knowledge gaps, encourage engagement, reduce duplication and facilitate translation of evidence into clinical practice. Methods: A two‐stage electronic Delphi survey process was undertaken by senior medical, nursing, education and social work staff at the Royal Children's Hospital, Victoria. Survey 1 collected demographic data and audit and research ideas following a series of open‐ended questions. Priority themes were defined as those that had more than four responses. Survey 2 used a 7‐point Likert ranking of these themes to generate a departmental audit and research prioritisation list. Results: 72/89 (82%) available senior staff responded to survey 1 and 63/83 (76%) responded to survey 2. Survey 1 yielded 208 audit and 130 research topics. Survey 2 established a prioritised list of 17 audit and 14 research topics. Top audit themes were mental healthcare, patient flow, management of sepsis and delays in ED specialist referrals. Top research priorities were the management of sepsis, mental healthcare, management of patients with autism and the management of severe asthma. Conclusions: This Delphi study has provided departmental audit and research priorities that are perceived to be of importance across the multidisciplinary ED team. This methodology allows strategic allocation of limited resources and may increase staff engagement.